Increased risk of arterial thromboembolic events after Staphylococcus aureus bacteremia: A matched cohort study. Issue 2 (August 2015) - Mejer, N.; Gotland, N.; Uhre, M.L.; Westh, H.; Schønheyder, H.C.; Petersen, A.; Jensen, A.G.; Larsen, A.R.; Skov, R.; Benfield, T.; Danish Staphylococcal Bacteremia Study Group
Summary Objectives An association between infection and arterial thromboembolic events (ATE) has been suggested. Here we examined the risk of myocardial infarction (MI), stroke and other ATE after Staphylococcus aureus bacteremia (SAB). Methods Danish register-based nation-wide observational cohort study between 1995 and 2008 with matched control subjects from the general population. Results Within a year, 278 of 15, 669 SAB patients and 2570 of 156, 690 controls developed MI, stroke or another ATE. The incidence rates among SAB patients were highest within the first 30 days and decreased over a year. The adjusted relative risk of MI, stroke and other ATE during the first 30 days after SAB in patients compared to controls were 2.2 (95% CI: 1.6–3.1), 5.5 (95% CI: 3.8–8.3) and 15.5 (95% CI: 6.9–35), respectively. Compared to controls, the increased adjusted relative risk persisted for 30 days for MI, 180 days for stroke and one year for other ATE. Increasing age, hypertension, atrial flutter/fibrillation, prior ATE and endocarditis in SAB patients were associated with an increased risk of ATE. Conclusions SAB was associated with a short-term increased risk of ATE that persisted longer dependent on type of event. Studies are warranted to investigate treatment strategies to diminish ATE after SAB.